2018
DOI: 10.3389/fpls.2017.02207
|View full text |Cite
|
Sign up to set email alerts
|

Selenium Accumulation Characteristics and Biofortification Potentiality in Turnip (Brassica rapa var. rapa) Supplied with Selenite or Selenate

Abstract: Selenium (Se) is an essential trace element for humans. About 70% of the regions in China, including most of the Tibetan Plateau, are faced with Se deficiency problems. Turnip is mainly distributed around the Tibetan Plateau and is one of the few local crops. In the present study, we compared the absorption and translocation differences of Se (IV) selenite and Se (VI) selenate in turnip. The results showed that Se treatment, either by soil addition (0.2–2 mg Se kg−1 dry soil) or by foliar spraying (50–200 mg L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
28
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 60 publications
4
28
0
Order By: Relevance
“…It has been reported that the toxicity, bioavailability, and reactivity of Se depend on its chemical formula and its concentration . The samples treated with Se 6+ would be much more prone to selenosis than those treated with Se 4+ , regardless of the method applied (soil addition or foliar application) . In general, the inorganic forms of Se are relatively less beneficial than organic Se .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that the toxicity, bioavailability, and reactivity of Se depend on its chemical formula and its concentration . The samples treated with Se 6+ would be much more prone to selenosis than those treated with Se 4+ , regardless of the method applied (soil addition or foliar application) . In general, the inorganic forms of Se are relatively less beneficial than organic Se .…”
Section: Introductionmentioning
confidence: 99%
“…16 The samples treated with Se 6+ would be much more prone to selenosis than those treated with Se 4+ , regardless of the method applied (soil addition or foliar application). 17 In general, the inorganic forms of Se are relatively less beneficial than organic Se. 18 The epidemiologic evidence points to a higher level of toxicity than organic Se, particularly for those selenates found underground and in drinking water.…”
Section: Introductionmentioning
confidence: 99%
“…However, some studies showed that low concentrations of Se in other plant species enhance plant growth and DM accumulation (Hartikainen and Xue 1999, Xue et al 2001, Ebrahimi et al 2015 or do not affect either parameter (Hartikainen et al 1997, Djanaguiraman et al 2010. Recently Li et al (2018) reported that significant increase in turnip (B. rapa) DM was obtained with 0.5 Se mg kg -1 soil as SeVI or SeIV, which is higher than our soil application as SeVI. They also showed that the foliar application of SeVI and SeIV had no significant effect on plants biomass.…”
Section: Discussionmentioning
confidence: 57%
“…However, these areas are exposed to severe Se deficiency. In a previous study, we analyzed the absorption and translocation characteristics of selenite and selenate in turnip by soil addition or foliar spraying (Li et al, 2018 ). We reported that turnip may be a potential Se-indicator species, and Se (IV) should be mainly selected as artificial Se fertilizer for turnips (Li et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study, we analyzed the absorption and translocation characteristics of selenite and selenate in turnip by soil addition or foliar spraying (Li et al, 2018 ). We reported that turnip may be a potential Se-indicator species, and Se (IV) should be mainly selected as artificial Se fertilizer for turnips (Li et al, 2018 ). These results provided preliminary information on Se intake from turnip for local people, but the risk of Se biofortification, such as the assimilation of Se in plants and the effects of Se on turnip quality, is still unknown in turnips.…”
Section: Introductionmentioning
confidence: 99%